Injection: A Gender Perspective on Domestic Slavery - Karras, Ruth (Palgrave, 2023)
This “injection” comes from the point of view of a historian of slavery turned historian of sexuality. The history of sexuality sits very uneasily with the history of enslavement, however, because of the problem of agency and its relationship to consent. Historians must not erase the personhood of the enslaved and their ability to make choices; but the realm within which they make those choices is so constrained that recognizing their agency can be akin to blaming the victim or implying consent when it cannot really be given.
The Palgrave Handbook of Global Slavery Throughout History
PUBLISHED